Pengembangan LKPD Online Tingkat SD yang Terintegrasi Langsung dengan Sistem Pengerjaan dan Penilaian - Nugroho, Dicky Anggriawan (Indonesian Journal of Islamic Elementary Education, 2022)
This research aims to develop onlinelearning media based on students’ worksheets which can be accessed onlineand directly integrated with the work system and assessment system. Research-based research and Development(R&D) with the 4D model Developmentmethod. The subjects of this study were experts at SDN 03 Gejlig consisting of learning media experts, material experts and 6th grade students. The research was started by collecting data based on the results of interviews and direct observation, surveys onmedia from learning media experts, surveys on material from learning material experts, and surveys on students' learning motivation using Google Forms to get results that are easy to analyze. For data analysis techniques using quantitative descriptive analysis and hypothesis testing using simple linear regression. And the results of the analysis show that the elementary school-Level OnlineStudent Worksheet-based learning media is very feasible to develop and apply because of its effectiveness in influencing student motivation and facilitating the assessment system and work on students’ worksheets.